2018
DOI: 10.1136/bcr-2017-224148
|View full text |Cite
|
Sign up to set email alerts
|

Lymphedema secondary to limited cutaneous systemic sclerosis

Abstract: Systemic sclerosis (SSc) is an autoimmune connective tissue disease characterised by vascular abnormalities, immune system activation and fibrosis. Lymphatic involvement in SSc was described more recently and starts in early stages. This report describes a 46-year-old patient who developed over the last 2 years asymmetric lymphedema in lower extremities. Compromise in lymphatic drainage was confirmed by lymphoscintigraphy. She also presented Raynaud's phenomenon, a scleroderma pattern in nailfold capillaroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…There have been only four case reports of comorbid Raynaud's phenomenon and lymphedema, all of which involved patients with other systemic disease, namely, yellow nail syndrome (Awerbuch, ), Fabry disease (Usmani, Camacho, Elfenbein, & Reginato, ), systemic sclerosis (Moreira, Crespo, & Santos, ), and metastasis of a malignant tumor (Al‐Nahhas, Collins, Jawad, & McCready, ). The only treatment options for these patients were medication for the systemic disease or palliative therapy.…”
Section: Introductionmentioning
confidence: 99%
“…There have been only four case reports of comorbid Raynaud's phenomenon and lymphedema, all of which involved patients with other systemic disease, namely, yellow nail syndrome (Awerbuch, ), Fabry disease (Usmani, Camacho, Elfenbein, & Reginato, ), systemic sclerosis (Moreira, Crespo, & Santos, ), and metastasis of a malignant tumor (Al‐Nahhas, Collins, Jawad, & McCready, ). The only treatment options for these patients were medication for the systemic disease or palliative therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Although no appropriate medications for lymphedema exist, a few case studies reported that the diuretic FRS and the common anti-inflammatory corticosteroid PDN improved lymphedema. 37,38) In this study, we observed that FRS and PDN inhibited the increase in foot volume in hindlimb lymphedema rats. In support of the important role of inflammation, ketoprofen, a nonsteroidal anti-inflammatory drug (NSAID), restored edema and fibrosis in experimental lymphedema in mice due to the inhibition of 5-lipoxygenase-dependent leukotriene B4 (LTB4) production.…”
Section: Discussionmentioning
confidence: 50%